2019
DOI: 10.33151/ajp.16.705
|View full text |Cite
|
Sign up to set email alerts
|

Validated Pre-Hospital Stroke Scales to Predict Large Vessel Occlusion: A Systematic Review

Abstract: Background Occlusions of large cerebral vessels, including the internal carotid artery and middle cerebral artery, result in significant burden of morbidity. Treatment was previously limited to intravenous thrombolysis, however multiple studies have shown significant improvements when patients undergo endovascular clot retrieval. Early identification and triage to centres capable of delivering this is likely to contribute to improved outcomes. This systematic review aims to compare clinical assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Observational data have revealed that the more severe the stroke, the greater the likelihood of experiencing an LVO. Several simplified clinical scales have been studied for this purpose, but none of them achieved both high sensitivity and specificity, 17 and to date there is no clear evidence of their value for managing dispatch rules in the field.…”
Section: The Prehospital Challengementioning
confidence: 99%
“…Observational data have revealed that the more severe the stroke, the greater the likelihood of experiencing an LVO. Several simplified clinical scales have been studied for this purpose, but none of them achieved both high sensitivity and specificity, 17 and to date there is no clear evidence of their value for managing dispatch rules in the field.…”
Section: The Prehospital Challengementioning
confidence: 99%
“…Cévní mozková příhoda (CMP) patří celosvětově i v České republice mezi nejčastější příčiny úmrtí nebo invalidizace (Loudon et al, 2019). Aktuálně jsou k dispozici pro pacienty s ischemickou CMP dvě základní léčebné modality -intravenózní trombolýza a mechanická trombektomie (MT).…”
Section: úVodunclassified
“…Ischemic stroke is a leading cause of mortality and morbidity worldwide ( 1 ), and the recognition of stroke symptoms and prehospital stroke management represent critical bottlenecks in acute stroke management. The delay from the onset of stroke symptoms to hospital arrival is largely due to delayed activation by the patient/witness or failure of EMS crew to recognize stroke symptoms ( 2 4 ).…”
Section: Introductionmentioning
confidence: 99%